“By God’s Grace, Nothing Will Prevent Me”: Exploring Intentions to Implement School-Based Agricultural Education in Liberia - Haley Q. Traini; Ehi Ogwiji (Journal of International Agricultural and Extension Education, 2024)
Scholars emphasize the pivotal role of agricultural education in driving development in sub-Saharan Africa, and Liberia, facing challenges such as job shortages, a fragile economy, and a vulnerable post-war youth population, stands uniquely positioned to benefit from school-based agricultural education. This research is a part of a multi-institutional, grant-funded, randomly controlled longitudinal investigation that delves into the long-term outcomes of school-based agricultural education implementation in Liberia. Our study focuses on understanding the intentions of Liberian agriculture teachers, principals, and parents regarding the adoption of school-based agricultural education, including 4-H, within their schools and communities after three trainings. Participants underwent extensive training covering school-based agricultural education, 4-H and youth leadership, school demonstration farms, home entrepreneurship projects, and agricultural innovations. Post-training questionnaires, including quantitative and qualitative data, revealed unwavering determination among participants to implement school-based agricultural education, particularly 4-H and school demonstration farms. Perceived barriers included a lack of support from school administrators and parents and the need for physical resources and tools. Nevertheless, participants expressed passion for the model, foreseeing positive impacts on the youth and the country's agricultural economy. This research sheds light on the potential transformative effects of SBAE in Liberia, providing insights into challenges and motivations for implementation.
Keywords: agriculture education; Liberia; teacher training; SBAE; 4-H